2018
DOI: 10.1103/physrevmaterials.2.044601
|View full text |Cite
|
Sign up to set email alerts
|

Ordinary dielectric function of corundumlike αGa2O3 from 40 meV to 20 eV

Abstract: The linear optical response of metastable α-Ga 2 O 3 is investigated by spectroscopic ellipsometry. We determine the ordinary dielectric function from lattice vibrations up to the vacuum ultraviolet spectral range at room temperature for a sample with a (0001) surface. Three out of four E u infrared-active phonon modes are unambiguously determined, and their frequencies are in good agreement with density functional theory calculations. The dispersion of the refractive index in the visible and ultraviolet part … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 72 publications
4
31
0
Order By: Relevance
“…A higher bandgap of %5.6 eV has been reported for the metastable α À Ga 2 O 3 phase. [24,25] After the seminal paper by Watanabe et al, [26] which demonstrated UV lasing at 215 nm in h-BN single crystal grown under high-pressure and high-temperature conditions, a new competitor to AlN has emerged in the area of semiconductor materials for UVC applications. The first h-BN-based electroluminescent device in the deep-UV range was soon later realized.…”
Section: Introductionmentioning
confidence: 99%
“…A higher bandgap of %5.6 eV has been reported for the metastable α À Ga 2 O 3 phase. [24,25] After the seminal paper by Watanabe et al, [26] which demonstrated UV lasing at 215 nm in h-BN single crystal grown under high-pressure and high-temperature conditions, a new competitor to AlN has emerged in the area of semiconductor materials for UVC applications. The first h-BN-based electroluminescent device in the deep-UV range was soon later realized.…”
Section: Introductionmentioning
confidence: 99%
“…A small binding energy of 7 meV was found for the lowest ordinary transition and a hyperbolic (quasi 2-dimensional) exciton with large binding energy of 178 meV was observed for the M 1 -type (extraordinary) critical point transition. 22 In earlier work, Segura et al, 39 Kracht et al, 40 and Feneberg et al 36 reported on more limited spectroscopic investigations and obtained partial bandgap energy information in agreement with Hilfiker et al The anisotropic dielectric constant for photon energies far below the bandgap but far above optical phonon mode frequencies were obtained from IR ellipsometry measurements (ε ∞,⊥ =3.75 and ε ∞, =3.64), 26 which agreed reasonably well by extrapolation from the near IR ellipsometry analysis (ε ∞,⊥ = 3.86, ε ∞, = 3.76) and direct Cauchy model analysis (ε ∞,⊥ = 3.864, ε ∞, = 3.756) performed by Hilfiker et al 22,32 Of fundamental importance for device design and operation is precise knowledge of phonon mode properties and static dielectric constants. A complete picture for these properties has not emerged yet.…”
Section: Introductionmentioning
confidence: 93%
“…All of the TO modes were identified except for the lowest E u mode due to lack of access to the far-IR range. 26,36 Akaiwa et al currently report the highest mobility value achieved for tin-doped alpha phase gallium oxide at 65 cm 2 /(Vs). 41 Sharma and Singisetti predicted a low field isotropic average electron mobility of ≈ 220 cm 2 /(Vs) and suggested polar optical phonon scattering as the dominant limitation for electron density of 1.0 × 10 15 cm −3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics are dominant in -Ga 2 O 3 compared with -Ga 2 O 3 (Neal et al, 2017). In addition, -Ga 2 O 3 has a corundum structure, which forms a ternary system with indium oxide and aluminium oxide, enabling both bandgap engineering to produce a desired wavelength and function engineering to improve the characteristics using transition metals (Cr, Fe, V, Ti) (Feneberg et al, 2018). However, -Ga 2 O 3 undergoes a phase transition at high temperature (>700 C) involving a metastable state, which is an undesirable disadvantage; hence, the substrate cannot be fabricated by liquid-phase growth, and only heteroepitaxy growth occurs (Oshima et al, 2015;.…”
Section: Introductionmentioning
confidence: 99%